Comparison of Fermentation Using MA 11 and EM4 on the Physicochemical Characteristics of Rice Straw - Ardiyanto, Yogi; Sukaryani, Sri (Jurnal Biologi Tropis, 2025)
This research was conducted to evaluate the impact of using MA-11 and EM4 fermentation agents on the physical and chemical properties of rice straw silage. The experiment used a Completely Randomized Design (CRD) with three treatments and three replications: P0 (without fermentation), P1 (fermented with 3% MA-11), and P2 (fermented with 3% EM4). Observed variables included physical characteristics (color, aroma, and texture) and chemical composition (dry matter, ash, and pH). The results showed that fermentation using MA-11 and EM4 improved both the physical and chemical quality of rice straw silage. Physically, the fermented treatments produced a fresher aroma, brownish-yellow color, and softer texture compared to the control. Chemically, dry matter content increased from 81.65% (P0) to 84.74% (P1) and 85.60% (P2). Ash content increased significantly (P<0.01), with the highest value found in MA-11 treatment (13.35%), while pH decreased significantly from 6.00 (P0) to 4.00 (P1) and 3.75 (P2). It can be concluded that fermentation of rice straw using MA-11 and EM4 enhances the physical and chemical characteristics of silage. The MA-11 treatment provided the highest ash content, while EM4 produced a softer texture and fresher aroma. Both inoculants are recommended as effective biotechnological treatments for improving the nutritional quality of rice straw as livestock feed.